Hermie C. van Zyl: Nuwe-Testamentikus aan die Universiteit van die Vrystaat - D. F. Tolmie (Acta Theologica)
In this article an overview of the academic contribution of Prof. Hermie C. van Zyl, Professor in New Testament Studies at the Faculty of Theology, University of the Free State, is presented. After a brief biographic overview, his academic contribution is discussed under the following headings: Synoptic Gospels, Hermeneutics, New Testament Studies as academic discipline; editorial activities; Bible translation and public theology.